An Analysis of The Occurrence of Phrasal Verbs in Song Lyrics of Lana Del Rey - Budiono, Shantika Yose Videla; Lodong, Agnechia Friska Rivalny (Universitas Pahlawan Tuanku Tambusai, 2025)
A phrasal verb consists of two or three words that work together as a single grammatical unit. In this study, the researcher focuses on the syntactic and semantic analysis of phrasal verbs found in Lana Del Rey's song lyrics. The purpose of this study is to analyze the types of phrasal verbs found in Lana Del Rey's song lyrics and to examine how these phrasal verbs are constructed syntactically and semantically. This study uses a descriptive qualitative method. The data for this study are song lyrics from Lana Del Rey's album Born to Die. The instrument used in this study is tabulation. This study obtained song lyrics from Lana Del Rey's official account on Spotify and then highlighted the lines containing phrasal verbs. Lana Del Rey was chosen for this study because of the success of her albums, which have topped the Billboard charts in the United States. This study is expected to help readers enrich their vocabulary and serve as an example or additional reference for other researchers who wish to analyze phrasal verbs in song lyrics as part of their research. This study is also beneficial for students studying phrasal verbs. There are 8 phrasal verbs found in Lana Del Rey's album Born to Die. The most commonly used type is the intransitive-inseparable phrasal verb. Based on this data, we can identify the presence of phrasal verbs in the song lyrics and distinguish between phrasal verbs and verb phrases in song lyrics.